Chemical means of equipment protection during oil and gas fields operation - Ivanenko, Olena I.; Shabliy, Tetiana O.; Nosachova, Yuliia V.; Kosmyna, Mykola M. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2022)
In this article the problems associated with the corrosion processes of equipment in oil and gas production are analyzed. The basic anticorrosive methods and means used in modern conditions are considered. Taking into account the mechanism and conditions of corrosion processes in the extraction and transportation of oil-containing products and gas condensate, the chemical method of protection of the equipment was chosen for research. Both known inhibitors based on phosphonic acids and synthesized substances based on sulfonates, imidazolines, and diamines were used as chemicals in the research. As a result of the research, the effectiveness of protection of metals from corrosion depending on the composition of highly mineralized medium, metal type, inhibitor type, and its concentration was evaluated and the effectiveness of the developed scale stabilizer (sodium dimethylsulfonate phosphinate) was evalu- ated in comparison with known reagents. It is shown that the effectiveness of protection of metals from corrosion in aqueous-petroleum mixtures with alkylimidazoline inhibitors (derivatives of 4,5-dihydro-1,3-diazole or 4,5-dihydroimidazole) and inhibitors developed on the basis of sunflower oil and diethylenetriamine (AC-1), ethylenedi-amine (AC-2) reaches 90% in doses of 5 - 50 mg/dm3. In addition, corrosion processes are often accompanied by processes of deposition of hardness salts on the surface of the equipment, which leads to a significant complication in the operation of the equipment. Therefore, studies of the anti-scale properties of these reagents under harsh conditions were performed. Real concomitant gas production waters were used as the medium. It was found that sodium di-methylsulfonate phosphinate is a very effective stabilizer of scale formation and is not inferior in effectiveness to known antiscalants. The proposed reagents can be used to stabilize water-oil mixtures and associated formation waters formed during the production and transportation of oil and gas.